Potential Risk of Red Flour Beetle Pest in Various Stored Grains - Strassburg, Melissa; Strassburg, Meghan; Phillips, Thomas (My University, 2017)
Red flour beetles are major pests in the U.S. They can often be found in stored grain products, primarily flour [4]. They also seem to be heavily attracted to maize, another popular food source in many areas [1]. The red flour beetle can cause significant destruction in these stored grains through increasing mold, changing flour color, and eating/destroying much of what is stored [2]. Because of the major impact of these pests on these major stored grain sources, there has been much research on various ways of ridding or limiting the red flour beetle from our stored grains. Much of this research, however, focuses on maize or flour pest problems with little information on other popular stored grains. We decided to look into how diets of oats, pet food, and corn meal affected the generation and the potential for the red flour beetle to become pests in other stored grain products. By observing the difference in preference and reproduction, we can observe the potential risk to our other stored grain products becoming infested with red flour beetles. During our research, the red flour beetles seemed to prefer flour overall (except when given the choice of oats), but had similar reproduction patterns to the flour with corn meal and oats. Because of their preferences and reproduction rates red flour beetles can be a major concern for other stored grains, mainly in areas where no stored flour is in close proximity.